1978
DOI: 10.2134/jeq1978.00472425000700010010x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil, Cover Crop, and Nutrient Source on Amounts and Forms of Phosphorus Movement Under Simulated Rainfall Conditions

Abstract: Three soils (Toledo silty clay, Rossmoyne silt loam, and Wauseon sandy loam) in greenhouse microplots were treated with chemical, chemical + straw, and manure sources of N, P, and K, cropped or left bare, and subjected to simulated rainfall. Phosphorus moving in runoff sediments, runoff solution, and leachate was measured. Most P moved as a component of sediments. Cropping decreased sediment and solution losses while manure generally increased losses in both. Most P moving in runoff solution was inorganic. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This nutrient tends to be held in the soil and little is transported to groundwaters (Reddy et al ., 1978 ;Conesa et al, 1979) . However, higher phosphate content in groundwater than in surface water has been reported for a desert stream in Arizona (Valett et al, 1990), and a Northern Michigan river (Hendricks & White, 1991) .…”
Section: Comparison Between Gravel Bar and Alluvial Plain Groundwatermentioning
confidence: 99%
“…This nutrient tends to be held in the soil and little is transported to groundwaters (Reddy et al ., 1978 ;Conesa et al, 1979) . However, higher phosphate content in groundwater than in surface water has been reported for a desert stream in Arizona (Valett et al, 1990), and a Northern Michigan river (Hendricks & White, 1991) .…”
Section: Comparison Between Gravel Bar and Alluvial Plain Groundwatermentioning
confidence: 99%
“…The 3-years mean PP losses were lower by 69, 58, and 89% from wheat/corn, wheat/cotton, and wheat/soybean, respectively, when compared with wheat/fallow. Reddy et al (1978) also found that their cropped plot decreased PP losses compared with the bare plot. The temporal distribution of PP losses varied across the four treatments (Fig.…”
Section: P Concentrations In Surface Runoffmentioning
confidence: 82%
“…There was also marked similarity between the mean summer EPC of suspended particles in the runoff and the mean, flow-weighted concentration of SRP of the runoff, suggesting equilibrium control of SRP. Reddy et al (1978) also found that manure amendments increased the EPC of soils tremendously.…”
Section: Eight-mile Runmentioning
confidence: 85%